Safety and efficacy of Monteban® G100 (narasin) for chickens for fattening. (20th November 2018) - ; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Durjava, Mojca Kos; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: The feed additive Monteban ® G100, containing the active substance narasin, an ionophore anticoccidial, is intended to control coccidiosis in chickens for fattening at a dose of 60–70 mg/kg complete feed. Narasin is produced by fermentation. Limited data on the taxonomic identification of the production strain did not allow the proper identification of strain NRRL 8092 as Streptomyces aureofaciens . The FEEDAP Panel cannot conclude on the absence of genetic determinants for antimicrobial resistance in Streptomyces spp. under assessment. Based on the available data set, the FEEDAP Panel cannot conclude on the safety of Monteban ® G100 for chickens for fattening. The simultaneous use of Monteban ® G100 and certain antibiotic drugs (e.g. tiamulin) is contraindicated. Narasin is not genotoxic. No indication of carcinogenicity or developmental toxicity was found at the doses tested in the mouse, rat and rabbit. The lowest no observed effect level (NOEL) identified in the oral toxicity studies was 0.5 mg/kg body weight (bw) per day for the neuropathy seen in a one‐year dog study. The acceptable daily intake (ADI) derived from this NOEL is 0.005 mg narasin/kg bw applying a uncertainty factor of 100. Monteban ® G100 is safe for the consumer. Maximum residue limits (MRLs) of 50 μg narasin/kg for all wet tissues ensure consumer safety. Monteban ® G100 is irritatant to the eyes but not to the skin. It has the potential to induce skin sensitisation. Inhalation exposure would pose a risk to persons handling the additive. Narasin, when used as a feed additive for chickens for fattening at 70 mg/kg feed, is not expected to pose a risk to the environment. The risk for sediment compartment cannot be assessed. The FEEDAP Panel cannot conclude on the efficacy of Monteban ® at the minimum applied dose of 60 mg narasin/kg complete feed for chickens for fattening.